Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1257/aer.20190830
|View full text |Cite
|
Sign up to set email alerts
|

How Research Affects Policy: Experimental Evidence from 2,150 Brazilian Municipalities

Abstract: Can research findings change political leaders’ beliefs and policies? We use experiments with 2,150 Brazilian municipalities to measure mayors’ demand for and response to research information. In one experiment, we find that mayors are willing to pay to learn the results of evaluation studies, and update their beliefs when informed of the findings. They value larger-sample studies more, while not distinguishing between studies in rich and poor countries. In a second experiment, we find that informing mayors ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 66 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…Akhmedov and Zhuravskaya (2004), Finan (2008), andRepetto (2018) find that the extent of policy transparency is strongly linked to political outcomes like public spending, budget deficits, or prospects of re-election for incumbent politicians. Hjort et al (2021) show that informing Brazilian mayors about the effectiveness of policies to enhance tax compliance increases the probability of such policies being implemented. Geys and Sørensen (2019) use a survey experiment to study how politicians change their preferences for school reforms when confronted with local school-performance data.…”
Section: Literature Contributionsmentioning
confidence: 97%
“…Akhmedov and Zhuravskaya (2004), Finan (2008), andRepetto (2018) find that the extent of policy transparency is strongly linked to political outcomes like public spending, budget deficits, or prospects of re-election for incumbent politicians. Hjort et al (2021) show that informing Brazilian mayors about the effectiveness of policies to enhance tax compliance increases the probability of such policies being implemented. Geys and Sørensen (2019) use a survey experiment to study how politicians change their preferences for school reforms when confronted with local school-performance data.…”
Section: Literature Contributionsmentioning
confidence: 97%
“…Zelizer (2018) randomly assigned policy briefings for staffers in a U.S. state legislature and those briefings increased bill co-sponsorship 60% above baseline rates on relevant legislation. In an experiment with 2,150 Brazilian municipalities, Hjort et al (2021) found that providing information on the efficacy of taxpayer reminder letters increased actual uptake of the policy by 10%.…”
Section: Psychological Barriers To the Use Of Scientific Evidence In ...mentioning
confidence: 99%
“…Additionally, research on decision making and motivated reasoning shows that politicians are inclined to interpret new information in light of previous beliefs and opinions (Bolsen and Palm, 2019). Experimental studies, for example, find that politicians are often biased by partisan convictions when confronted with contradicting evidence (Baekgaard et al, 2019; Hjort et al, 2021; Lee, 2021) and that political positions can even be reinforced as a response to science (e.g. Heikkila et al, 2020).…”
Section: Previous Research: Partisanship and Research Usementioning
confidence: 99%